2016
DOI: 10.3892/ijo.2016.3488
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin inhibits gefitinib-resistant lung cancer cells by suppressing EGFR/ERK/MMP-12 and CIP2A/Akt signaling pathways

Abstract: Oridonin (Ori), a diterpenoid compound extracted from traditional medicinal herbs, elicits antitumor effects on many cancer types. However, whether Ori can be used in gefitinib-resistant non-small cell lung cancer (NSCLC) cells remains unclear. This study investigated the antitumor activity and underlying mechanisms of Ori. Results demonstrated that this compound dose-dependently inhibited the proliferation, invasion, and migration of the gefitinib-resistant NSCLC cells in vitro. Ori also significantly downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The transcription factor AP-1 may form either a homo-or hetero-complex which can bind as c-fos/c-fos, c-jun/c-jun or c-fos/c-jun to activate endogenous or exogenous motivation (37). AP-1 is also a critical transcriptional modulator in ERK signal transduction (15). Moreover, the MMP7 and vimentin promoter region contains a cisregulatory element of one AP-1 binding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor AP-1 may form either a homo-or hetero-complex which can bind as c-fos/c-fos, c-jun/c-jun or c-fos/c-jun to activate endogenous or exogenous motivation (37). AP-1 is also a critical transcriptional modulator in ERK signal transduction (15). Moreover, the MMP7 and vimentin promoter region contains a cisregulatory element of one AP-1 binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences has shown that natural products not only serve key roles in the detection and evolvement of novel drugs, but they may be used as molecular probes for screening treatment targets (14,15). Paris polyphyllin is a Polyphyllin I inhibits invasion and epithelial-mesenchymal transition via CIP2A/PP2A/ERK signaling in prostate cancer medicinal herb in the Shennongjia National Nature Reserve of China, which may treat fevers, headaches, burns, wounds, and exhibit immune-regulatory and antitumor abilities (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The beads were further incubated with 750 mM phosphopeptide in assay buffer for 10 min at 30˚C with constant agitation. 100 µl of Malachite Green Phosphate Detection Solution was added and the absorbance at 650 nm was measured on a microplate reader (27).…”
Section: Reagentsmentioning
confidence: 99%
“…In 2016, Yang et al (20) reported that the ERK signal pathway may serve important functions in 5-FU-mediating of colorectal cancer. Xiao et al (21) identified that Oridonin inhibits gefitinib-resistant lung cancer cells by suppressing ERK and AKT signaling pathways. In the present study, it was identified that VASH1 downregulated P-gp expression by blocking the AKT signal pathway, thus inhibiting ADR resistance of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%